Cultural Care Practices Provided at Home by the Zenú Indigenous Mothers to their Premature Children and to Those with Low Birth Weight - Ortiz Anaya, Yalena; Rojas, Juan Guillermo (Investigación y Educación en Enfermería, 2023)
Objective. The work’s aim was to comprehend the cultural practices of the care by Zenú indigenous mothers to their newborn premature children and those of low birth weight by implementing the Kangaroo-Mother method at home. Methods. Qualitative study of particularistic ethnographic approach, with participation from eight mothers and two key informants trained in the Kangaroo-Mother method, who were interviewed and observed in their homes, in the municipalities of San Andrés de Sotavento, Tuchín, Sampués, and San Antonio de Palmitos from the Departments of Córdoba and Sucre (Colombia), respectivelyEthnographic analysis was performed. The criteria of data saturation and methodological rigor, typical of qualitative research, were applied. Results. Eight Zenú indigenous mothers and two key informants from the family participated in the study. The themes emerging were the context, a different experience, adaptations of the Kangaroo-Mother method at home and care practices, protection and healing based on customs and cultural tradition. Conclusion. The indigenous mothers provide holistic care to their newborn premature children and those with low birth weight, by integrating the knowledge and practices of the Kangaroo-Mother method and with the ancestral practices of care, protection, and healing characteristic of the context and culture; thus, transcending the use of resources available in the environment.